The dynamic characteristic and hysteresis effect of an air spring - Welsch, Michael; Löcken, Florian (Zielona Góra: Uniwersytet Zielonogórski)
In many applications of vibration technology, especially in chassis, air springs present a common alternative to steel spring concepts. A design-independent and therefore universal approach is presented to describe the dynamic characteristic of such springs. Differential and constitutive equations based on energy balances of the enclosed volume and the mountings are given to describe the nonlinear and dynamic characteristics.
Keywords: air springs; dynamic characteristics; transfer thermodynamic to mechanic